STIK KEJU BERBASIS BAHAN LOKAL KAYA ANTIOKSIDAN: SUBSTITUSI EKSTRAK BUNGA TELANG DAN TEPUNG UBI JALAR UNGU - Nuristha Febrianti; Febr Yolanda Pasau; Lilik Sofiatus Solikhah (Jurusan Ilmu dan Teknologi Pangan Universitas Halu Oleo, 2025)
This study aimed to develop an alternative snack rich in antioxidants and to examine differences in acceptability and nutrient content among formulations. A completely randomized design (CRD) was used with three formulations combining butterfly pea flower extract and purple sweet potato flour: F1 (50%:50%), F2 (65%:35%), and F3 (70%:30%). Organoleptic testing was conducted with 30 semi-trained panelists using a 7-point hedonic scale, while nutritional analysis measured antioxidant content, carbohydrates, protein, and fiber. The sensory evaluation found no significant differences (p>0.05) in color, aroma, taste, and texture. However, the nutritional analysis showed significant differences (p<0.05) in antioxidant, carbohydrate, and protein contents, but not in fiber levels. F1 had the highest antioxidant content (89.10 ppm), with carbohydrate at 13.91%, protein at 6.20%, and fiber at 8.16%. Based on these results, F1 was identified as the best formulation and shows potential for development as a healthy, locally sourced snack with high antioxidant content.